Gender differences in medical errors among older patients and inequalities in medical compensation compared with younger adults - Liu, Paicheng; Yang, Yuxuan; Cheng, Jianxin (Frontiers in Public Health, 2022)
Background Despite growing evidence focusing on health inequalities in older adults, inequalities in medical compensation compared with younger adults and gender disparities of medical errors among older patients have received little attention. This study aimed to disclose the aforementioned inequalities and examine the disparities in medical errors among older patients. Methods First, available litigation documents were searched on “China Judgment Online” using keywords including medical errors. Second, we compiled a database with 5237 disputes. After using systematic random sampling to retain half of the data, we removed 549 unrelated cases. According to the age, we identified 424 and 1563 cases related to older and younger patients, respectively. Then, we hired two frontline physicians to review the documents and independently judge the medical errors and specialties involved. A third physician further considered the divergent results. Finally, we compared the medical compensation between older and younger groups and medical errors and specialties among older patients. Results Older patients experienced different medical errors in divergent specialties. The medical error rate of male older patients was over 4% higher than that of females in the departments of general surgery and emergency. Female older patients were prone to adverse events in respiratory medicine departments and primary care institutes. The incidence of insufficient implementation of consent obligation among male older patients was 5.18% higher than that of females. However, females were more likely to suffer adverse events at the stages of diagnosis, therapy, and surgical operation. The total amount of medical compensation obtained by younger patients was 41.47% higher than that of older patients. Conclusions Except for the common medical errors and departments involved, additional attention should be paid to older patients of different genders according to the incidence of medical errors. Setting up the department of geriatrics or specialist hospitals is also an important alternative to improve patient safety for older people. Furthermore, there may be inequality in medical compensation in older patients due to the tort liability law of China.